ショウワキチ デ カンソク サレル TAKABATIC フウ ニ ツイテ 1 - 守田, 康太郎; モリタ, ヤスタロウ; MORITA, Yasutaro (国立極地研究所, 1968)
P(論文) The wind regime at Syowa Station, located on the East Ongul Island 4km apart from the coast of Antarctica, is analyzed to explain the seaward effect of katabatic winds. 1. Rather strong (6-17m/s) easterly winds of katabatic origin prevail at night in summer season. The type of diurnal variation of wind velocity, then, is quite different from the ordinary type observed at middle to lower latitudes. 2. Disturbances of synoptic scale often destroys such a diurnal variation, though weak disturbances sometimes accelerate the night-time winds of katabatic origin. 3. Winds of katabatic origin can be distinguished from those by synoptic scale disturbances through the following points : (a) Regularity of the time of onset and end. (b) Decrease in temperature with increase in wind velocity. (c) A slight clockwise deviation of wind direction compared with the prevailing direction by synoptic scale phenomena. 4. The diurnal variation of wind velocity vanishes in winter season, when the persistent northeast-easterly winds of katabatic origin blow day and night. These winds, in most cases in winter, are associated with the synoptic scale disturbances, and it is difficult to distinguish pure katabatic winds from the latter. 5. Typical behaviours of katabatic winds, as exemplified by the sudden onset and end, abrupt changes in pressure and extraordinary intensity of winds, are not observed at Syowa Station where the phenomena are generally mild compared with those at other Antarctic stations. It is supposed that the location of Syowa Station is at about the critical distance of the seaward effect of katabatic winds, so that the effect reaches Syowa Station only when the conditions on the ice slope of the continent are favourable enough to cause the katabatic "type 2" in BALL'S theory, and that the base is covered with the seaward moving air of higher depth beyond the hydraulic jump line. 6. Further researches on the behaviour of the katabatic winds at the seaward site are intended through the analysis of recent data ...